2019
DOI: 10.1186/s13567-019-0667-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hyopneumoniae evades phagocytic uptake by porcine alveolar macrophages in vitro

Abstract: Mycoplasma hyopneumoniae , the agent of porcine enzootic pneumonia (EP), is able to persist in the lung tissue and evade destruction by the host for several weeks. To understand the mechanism of pathogen survival, phagocytic uptake of M. hyopneumoniae by primary porcine alveolar macrophages was investigated. Intracellular location and survival of the pathogen were explored using gentamicin survival assays, flow cytometry and confocal microscopy of M. hyopneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…IFN-γ promotes the activation and proliferation of T cells and macrophages, which play vital roles in host defenses in the lungs. Previous studies showed that macrophage dysfunction was induced by Mycoplasma spp., including M. bovis, and promoted persistent infection (2,(66)(67)(68). Immune reactivation by combination therapy of anti-PD-L1 mAb with COX-2 inhibitor could help in the development of potential methods for the control of M. bovis infection.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ promotes the activation and proliferation of T cells and macrophages, which play vital roles in host defenses in the lungs. Previous studies showed that macrophage dysfunction was induced by Mycoplasma spp., including M. bovis, and promoted persistent infection (2,(66)(67)(68). Immune reactivation by combination therapy of anti-PD-L1 mAb with COX-2 inhibitor could help in the development of potential methods for the control of M. bovis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, specific IgG diffusing from the blood into the lung tissue or produced locally in the BALT could opsonize M. hyopneumoniae , resulting in phagocytosis by macrophages and neutrophils [ 53 ]. However, Deeney et al [ 54 ] recently reported that addition of convalescent porcine sera did not enhance engulfment of M. hyopneumoniae by alveolar macrophages in vitro.…”
Section: Interactions Of M Hyopneumoniae With the Hostmentioning
confidence: 99%
“…Gram-negative and Gram-positive bacteria have at least 6 reported secretion/translocation systems [126]. The general secretory (Sec) pathway comprises an essential, ubiquitous and universal export machinery for most proteins that translocate through (soluble secretome) or integrate into (insoluble secretome) the cell membrane [127]. In mycoplasmas, however, the Sec secretory pathway is apparently incomplete, as some genes coding for components of this pathway were not found in their genomes.…”
Section: Protein Secretion Of M Hyopneumoniae and Its Impact On Pathmentioning
confidence: 99%